2010
DOI: 10.1016/j.devcel.2009.11.015
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Regulation of Protrusion and Polarity by PI(3)K during Neutrophil Motility in Live Zebrafish

Abstract: Summary Cell polarity is crucial for directed migration. Here we show that phosphoinositide 3-kinase (PI(3)K) mediates neutrophil migration in vivo by differentially regulating cell protrusion and polarity. The dynamics of PI(3)K products PI(3,4,5)P3-PI(3,4)P2 during neutrophil migration were visualized in living zebrafish, revealing that PI(3)K activation at the leading edge is critical for neutrophil motility in intact tissues. A genetically encoded photoactivatable Rac was used to demonstrate that localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
412
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(440 citation statements)
references
References 64 publications
27
412
1
Order By: Relevance
“…S8 C and E). These findings are consistent with previous reports that the photoactivation of Rac at the leading edge of the cell can rescue the protrusion defects induced by PI3K inhibition (27,28). PI3K is not required for the protrusion.…”
Section: Plekhg3 Enhances Polarized Cell Migration Via a Positive Feesupporting
confidence: 83%
“…S8 C and E). These findings are consistent with previous reports that the photoactivation of Rac at the leading edge of the cell can rescue the protrusion defects induced by PI3K inhibition (27,28). PI3K is not required for the protrusion.…”
Section: Plekhg3 Enhances Polarized Cell Migration Via a Positive Feesupporting
confidence: 83%
“…The mechanisms that regulate the decision to disassemble or to elongate and grow are not understood. However, these mechanisms are likely the regulators of the directed migration of mesenchymal cells and may also contribute to directional decision-making during pseudopod selection by amoeboid cells migrating in vitro (Andrew and Insall 2007) and in vivo (Cvejic et al 2008;Yoo et al 2010).…”
Section: Turnover Of Adhesions In Protrusionsmentioning
confidence: 99%
“…Ample evidence has indicated that the PI3K-Akt pathway controls the directionality of leukocyte chemotactic migration (1). In zebrafish embryos, the PI3Kg-Akt pathway promotes Racmediated actin polymerization around the leading edge, which guides leukocyte migration in vivo (32). To determine which pathways are involved in vibsanin B's inhibitory effect on leukocyte migration, we analyzed the alterations of selected pathways, including the PI3K-Akt pathway in THP-1 cells and zebrafish embryos upon vibsanin B treatment.…”
Section: Inactivation Of Hsp90 Abrogates Leukocyte Migrationmentioning
confidence: 99%